Single Cell Transcriptomic Analysis of Spinal Dmrt3 Neurons in Zebrafish and Mouse Identifies Distinct Subtypes and Reveal Novel Subpopulations Within the dI6 Domain - Iglesias González, Ana Belén; Jakobsson, Jon E. T.; Vieillard, Jennifer; Lagerström, Malin C.; Kullander, Klas; Boije, Henrik (Frontiers in Cellular Neuroscience, 2021)
The spinal locomotor network is frequently used for studies into how neuronal circuits are formed and how cellular activity shape behavioral patterns. A population of dI6 interneurons, marked by the Doublesex and mab-3 related transcription factor 3 (Dmrt3), has been shown to participate in the coordination of locomotion and gaits in horses, mice and zebrafish. Analyses of Dmrt3 neurons based on morphology, functionality and the expression of transcription factors have identified different subtypes. Here we analyzed the transcriptomes of individual cells belonging to the Dmrt3 lineage from zebrafish and mice to unravel the molecular code that underlies their subfunctionalization. Indeed, clustering of Dmrt3 neurons based on their gene expression verified known subtypes and revealed novel populations expressing unique markers. Differences in birth order, differential expression of axon guidance genes, neurotransmitters and their receptors, as well as genes affecting electrophysiological properties, were identified as factors likely underlying diversity. In addition, the comparison between fish and mice populations offers insights into the evolutionary driven subspecialization concomitant with the emergence of limbed locomotion.